Risk factors of gastrointestinal bleeding after cardiopulmonary bypass in children: a retrospective study - Li, Zheng-Qing; Zhang, Wei; Guo, Zheng; Du, Xin-Wei; Wang, Wei (Frontiers in Cardiovascular Medicine, 2023)
Background: During cardiac surgery that involved cardiopulmonary bypass (CPB) procedure, gastrointestinal (GI) system was known to be vulnerable to complications such as GI bleeding. Our study aimed to determine the incidence and risk factors associated with GI bleeding in children who received CPB as part of cardiac surgery.Methods: This retrospective study enrolled patients aged <18 years who underwent cardiac surgery with CPB from 2013 to 2019 at Shanghai Children's Medical Center. The primary outcome was the incidence of postoperative GI bleeding in children, and the associated risk factors with postoperative GI bleeding episodes were evaluated.Results: A total of 21893 children who underwent cardiac surgery with CPB from 2013 to 2019 were included in this study. For age distribution, 636 (2.9%) were neonates, 10984 (50.2%) were infants, and 10273 (46.9%) were children. Among the 410 (1.9%) patients with GI bleeding, 345 (84.2%) survived to hospital discharge. Incidence of GI bleeding in neonates, infants and children were 22.6% Risk Factors of GI Bleeding 2 (144/636), 2.0% (217/10984) and 0.5% (49/10273), respectively. The neonates (22.6%) group was associated with highest risk of GI bleeding. Patients with GI bleeding showed longer length of hospital stays (25.8 ± 15.9 vs. 12.5 ± 8.9, P < 0.001) and higher mortality (15.9% vs. 1.8%, P < 0.001). Multivariate logistic regression analysis showed that age, weight, complicated surgery, operation time, use of extracorporeal membrane oxygenation (ECMO), low cardiac output syndrome (LCOS), hepatic injury, artery lactate level, and postoperative platelet counts were significantly associated with increased risk of GI bleeding in children with congenital heart disease (CHD) pediatric patients that underwent CPB procedure during cardiac surgery.The study results suggest that young age, low weight, long operation time, complicated surgery, use of ECMO, LCOS, hepatic injury, high arterial lactate level, and low postoperative platelet counts are independently associated with GI bleeding after CPB in children.This retrospective study was carried out and approved by the Ethical Committee of Shanghai Children's Medical Center. Medical files of all patients who underwent cardiac surgery with CPB